2022
DOI: 10.3389/fcvm.2022.899235
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Angiotensin Receptor Neprilysin Inhibitor in Cardiovascular Diseases: A Bibliometric Review From 2000 to 2022

Abstract: Cardiovascular disease (CVD) has become a huge challenge for the global public health system due to its high morbidity, mortality and severe economic burden. In recent years, angiotensin receptor neprilysin inhibitor (ARNI), a new class of drugs, has shown good therapeutic effects on CVD patients in several clinical studies, reducing the morbidity and mortality of CVD patients. In this study, we retrieved publications on ARNI research in the cardiovascular field from the Web of Science core collection and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Keywords are succinct summary of the research content of a paper, and analyzing high-frequency keywords can reveal the main research topics in a given field ( Xu et al, 2022 ; Yang J. et al, 2023 ; Zhang G. et al, 2023 ). Figure 9 presents the co-occurrence relationships between keywords that appeared no less than 20 times, where the color of the nodes leaning toward warmer shades of red indicates the later average appearance time of the corresponding keyword.…”
Section: Resultsmentioning
confidence: 99%
“…Keywords are succinct summary of the research content of a paper, and analyzing high-frequency keywords can reveal the main research topics in a given field ( Xu et al, 2022 ; Yang J. et al, 2023 ; Zhang G. et al, 2023 ). Figure 9 presents the co-occurrence relationships between keywords that appeared no less than 20 times, where the color of the nodes leaning toward warmer shades of red indicates the later average appearance time of the corresponding keyword.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars usually use high-frequency keywords to reflect the hot issues in the research field. 26 At this stage, keywords with similar meanings, such as “transcranial direct current stimulation”, “direct current stimulation”, and “dc stimulation” were combined together. The left of Figure 7 depicted the final merged keyword co-occurrence map.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, although Yaffe K was not the author with the highest number of publications, she had the highest TGCS ( 7333) and H-index (123), indicating the importance of his research. The most frequently co-cited authors derived from the references are commonly used as a significant indicator to measure the author's contribution to this field (Xu et al, 2022a). Visualization of the network of co-cited authors is shown in Figure 5B.…”
Section: Analysis Of Authors and Co-cited Authormentioning
confidence: 99%